Planning in Dublin: goals achieved and opportunities lost - McCarron, Gay (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
The title suggests that this paper might produce a form of balance sheet with a list of 'Goals Achieved ' on one side and 'Opportunities Lost' on the other and the summing up of both lists would indicate whether the operation of the planning system over the last forty years could be judged a 'Success ' or a ' Failure' . However, such an assessment is inherently more complex. There has been constant change in the social, cultural, economic and demographic sphere - sometimes massive and sometimes going in contrary directions, as well as administration changes, change in values, slumps and booms, stop and go, even climate change. Accordingly, the exciting task of identifying and agreeing on a wide range of meaningful goals or opportunities and the evaluation of whether these are either goals achieved or opportunities lost would require a lengthier examination. What I aim to do, therefore, is to try and identify what the Government at the time hoped to achieve with the 'Physical Planning System' that was to be established and underpinned by the Local Government (Planning and Development) Act 1963. What were their Goals in this new endeavour? As to whether these Goals were achieved or not, I hope to offer some personal thoughts. In looking at, and seeking to evaluate, the Goals identified, I believe it is also necessary to try and get some understanding of the life and times in Ireland in the fIfties and early sixties as they are so vastly different from those that followed and from those of today's - post- Celtic Tiger - Ireland.
Papers from practice
Keywords: Urban geography -- Ireland